2019
DOI: 10.1002/acm2.12798
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and homogenization of image noise between two CT scanner models

Abstract: Feedback from radiologists indicated that differences in image appearance and noise impeded reading of post-contrast computed tomography (CT) scans from an updated CT scanner that was recently added to a fleet of existing scanners from the same vendor, despite using identically named reconstruction algorithms. The goals of this work were to quantify and possibly standardize image quality on the new and an existing scanner using phantom images. Three months of daily quality control images were analyzed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Noise is an essential parameter in the CT image quality [ 12 , 27 ], and its suppression in QCT is used to enhance the accuracy of diagnosis [ 33 - 35 ]. Cruz-Bastida et al [ 36 ] reported that noise reduction in two phantoms (head and Catphan phantoms) significantly declines CT number bias, resulting in improving CT number accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Noise is an essential parameter in the CT image quality [ 12 , 27 ], and its suppression in QCT is used to enhance the accuracy of diagnosis [ 33 - 35 ]. Cruz-Bastida et al [ 36 ] reported that noise reduction in two phantoms (head and Catphan phantoms) significantly declines CT number bias, resulting in improving CT number accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [35] have shown that the characteristics of the extracted features may depend on non-tumor related factors like the signal-to-noise ratio of the experimental data. Therefore, in the case of studies that utilize data from more than one scanner, data homogenization should be implemented prior to the data extraction process [36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to carry out further studies on this issue. The development of automatic measurements on AAPM CT performance phantom for all measurement parameters other than SSP (such as noise [25], low-contrast detectability [21], mechanical alignment, beam hardening, spatial resolution [26], HU linearity [27], and so on) may give great benefit to medical physicists in implementing quality control programs. Nevertheless, it still poses a challenge for future studies.…”
Section: Field Of View Variationmentioning
confidence: 99%